The Impact of Managerial Ownership, Capital Structure, Profitability, and Firm Size on Firm Value - Jenny Putri Setyawan; Ai Hendrani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Firm value is an important indicator that reflects investors' perceptions of a company's performance and future prospects. This study aims to examine the effects of managerial ownership, capital structure, profitability, and firm size on firm value. The study focuses on companies in the basic materials and chemicals sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative approach with a causal research design was employed using secondary data obtained from the companies' annual financial statements. The sample was selected using purposive sampling, resulting in 17 companies with a total of 85 observations after data screening and processing. Data were analyzed using multiple linear regression with the assistance of IBM SPSS software. The results indicate that, partially, managerial ownership and capital structure have a positive and significant effect on firm value. Furthermore, managerial ownership, capital structure, profitability, and firm size jointly have a significant effect on firm value. These findings are expected to provide valuable insights for investors and corporate management in making decisions aimed at enhancing firm value.